Stok Karbon dan Biomasa Beberapa Komoditas Tanaman Pertanian Di Bodogol- Taman Nasional Gunung Gede Pangrango â Jawa Barat - Rahajoe, Joeni Setijo; Alhamd, Laode; Handayani, Dewi (Perhimpunan Biologi Indonesia, 2016)
ABSTRACTThe study of carbon stock and biomasa of agricultural commodities was conducted in the Bodogol village, Gunung Gede Pangrango National Park - West Java. The purpose of this research to determine the biomasa, carbon stock and the rate of decomposition of agricultural commodities by using destructive sample and litterbag method. Six of agricultural commodities: green beans/buncis (Phaseolus vulgaris), chilli (Capsicum annum), corn (Zea mays), bean (Vigna cylindrica), peanuts (Arachis hypogaea) and cassava (Manihot esculenta), were calculated their biomasa and carbon stocks. The result showed that the biomasa of agriculture commodities in the range of 0.152 to 4.216 t ha-1, with a carbon stock ranging from 0.01 to 1.83 t ha-1. The decomposition rate (k) of those commodities were k = 5.6 y-1; 5.48 y-1, 5.18 y-1, 5.04 y-1, 4.42 y-1, and k = 1.21 y-1, for Manihot esculenta, Vigna cylindrica, Arachis hypogea, Zea mays, Capsicum annum and Phaseolus vulgaris, respectively.Keywords: Biomasa, Gede Pangrango, Carbon, Agricultural commodities